IMROAH LAINA PENGGUNAAN PENDEKATAN REGRESIF & LIVING HISTORY SEBAGAI STRATEGI PERWUJUDTAN SDG'S MENUJU INDONESIA EMAS 2045: PENGGUNAAN PENDEKATAN REGRESIF & LIVING HISTORY SEBAGAI STRATEGI PERWUJUDTAN SDG'S MENUJU INDONESIA EMAS 2045 - Kusuma, Imroah Laina Retno Mukti (UPT Perpustakaan Universitas Jambi, 2026)
Education plays a strategic role in improving the quality of human resources and supporting the achievement of the Sustainable Development Goals (SDGs), particularly the goal of quality education. However, challenges to the quality of education in Indonesia remain serious, including in history learning, which is often rote and lacks context. This study aims to examine the use of the regressive approach and living history as history learning strategies in realizing quality education oriented towards the SDGs towards Indonesia Emas 2045. This study uses a qualitative descriptive method with a library research approach, through analysis of scientific literature, reputable journals, and relevant policy documents. The results of the study indicate that the regressive approach, which begins learning from contemporary issues and moves towards historical exploration of the past, can increase the relevance of history learning and develop students' critical thinking skills. Meanwhile, living history emphasizes direct learning experiences based on local history through observation, interviews, and environmental exploration, thereby fostering historical awareness, national values, and social responsibility. The integration of these two approaches is considered aligned with the principles of sustainable education and the Independent Curriculum because it encourages contextual, reflective, and participatory learning. Thus, the regressive and living history approaches have the potential to be effective pedagogical strategies in supporting the achievement of the SDGs.